Energy Consumption and Economic Growth Nexus in Nigeria: Evidence based on ARDL Bound Test Approach - Anochiwa, Lasbrey; Enyoghasim, Oguwuike Michael; Uma, Kalu E.; Obidike, C. Paul; Uwazie, Iyke Uwazie; Ogbonnaya, Ikwor Okoroafor; Ojike, O. Richard; Anyanwu, Clara Kelechi (International Journal of Energy Economics and Policy, 2020)
This study examines the relationship between economic growth and energy consumption in Nigeria by using ARDL Bound Test regression analysis. In the investigation process energy consumption, was disaggregated into electricity, coal and petroleum with growth rate of GDP data is used from 1980-2017. The findings show that petroleum and electricity variables are positive and significant to growth while coal is positive but not significant. Overall outcome is that energy consumption has a positive relationship with economic growth. The coal deposit must be put in use to increase energy production and consumption and stimulate other economic activities for growth Keywords: Energy consumption, economic growth, ARDL test. JEL Classifications: Q32, Q044 DOI: https://doi.org/10.32479/ijeep.10021